EXPLORING THE ROLE OF DIET IN ALLEVIATING SYMPTOMS OF PREMENSTRUAL SYNDROME [PMS]: A NARRATIVE REVIEW - Febriana, Romadhinniar; Sartika, Dian; Fernandes, Alcinda Pinto; Amalia, Fany Hardiati; Putri, Frilya Rachma (Journal of Psychiatry Psychology and Behavioral Research, 2026)
Introduction: Premenstrual Syndrome (PMS) involves physical and emotional symptoms that occur before menstruation, affecting most women of reproductive age. This study aims to review the role of nutrition and dietary interventions in alleviating PMS symptoms, with a focus on calcium, magnesium, vitamin D, and vitamin B6. Methods: Peer-reviewed articles from the past five years focused on nutrition and PMS. Data sources included PubMed, Google Scholar, and ScienceDirect. Keywords included "PMS," "nutrition/diet," "micronutrients/vitamins/minerals," and "dietary intervention/nutritional therapy." Articles were selected based on relevance and quality. Results: high intake of calcium, magnesium, vitamin D, and vitamin B6 reduces PMS symptoms. Calcium stabilizes mood and reduces anxiety. Magnesium alleviates pain and bloating. Vitamin D reduces inflammation and regulates immune function, while vitamin B6 supports neurotransmitter synthesis, helping reduce depression and fatigue. Discuss: High-fiber, low-sugar diets and omega-3 fatty acids from fatty fish also mitigate PMS symptoms. Nutritional interventions effectively manage PMS symptoms. A balanced, nutrient-rich diet should be integral to PMS management. Conclusion: Nutrition and diet play an important role in alleviating the symptoms of premenstrual syndrome (PMS). High intakes of calcium, magnesium, vitamin D, and vitamin B6 have consistently been proven to reduce various physical and psychological complaints experienced by women during the luteal phase of the menstrual cycle.  Keywords: premenstrual, diet, nutrition.